Dynamic Interaction between Oil Price, Stock Exchange and Exchange Rate: The Case of Kazakhstan - Urazov, Alibek (2010)
This study analyzes the impact of crude oil price fluctuations on Kazakhstan‟s stock market and its exchange rate against the US dollar. Kazakhstan‟s economy has been growing tremendously over the years attracting both individual and institutional investors. It is important for potential investors to identify the relationship and risk sharing factors between different assets of a portfolio. This study shows the cointegrating relationships between oil prices, Kazakhstan stock market and exchange rate. The VECM and Granger causality tests are applied to investigate the relationships and impacts between these variables. Total sample period is divided into three sub-samples in order to account for structural breaks which will provide more accurate results. The tests reveal that the oil price fluctuations do not granger causes the movements of the Kazakhstan stock market however there is the presence of cointegration between these variables. Lack of evidence for granger causality but presence of cointegration could be attributed to the indirect effect of oil price fluctuations on the finance sector of the Kazakhstan stock market. The second section of the analysis provides evidence that the impact of oil price fluctuations on the Kazakhstan exchange rate is minimal. This evidence moves in tandem with the fact the exchange rate is well monitored and regulated hence the fluctuations in oil price are not commonly reflected in the exchange rates. From the results obtained by running various tests, this study provides an insight to investors on the portfolio diversification possibilities available in the Kazakhstan market.